DIFFERENCES AND SIMILARITIES IN CROSS-CULTURAL SOCIAL TRUST AND MORAL VALUES (International scientific-electronic journal “Pioneering studies and theories”, 2025)
This article analyzes the formation of intercultural social trust, its manifestation in different societies, and the differences and similarities of moral values across cultures. The sources of trust, attitudes towards institutions, and the role of interpersonal relationships are highlighted using different cultural models—East and West, collectivist and individualist societies. The article substantiates the role of general moral principles (honesty, justice, responsibility) in strengthening global social trust. The research results demonstrate the importance of understanding differences and strengthening cooperation through similarities in the process of intercultural dialogue